HUBUNGAN DISMENORE DENGAN AKTIVITAS BELAJAR MAHASISWI - Dwi Pradnya Iswari (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2014)
Dysmenorrhea is painful cramps or tightness in the abdominal area, started in the 24 hours before the onset of menstrual bleeding can last 24-36 hours and weighed only lasted 24 hours. Dysmenorrhea is experienced by the student may have an impact on learning activities as learning activities are influenced by physiological aspects associated with the general physical fitness levels and marks can affect the spirit and intensity of students in upper division courses. The purpose of this study was to determine the relationship of dysmenorrhea with learning activities. This study was a non-experimental design is a correlational study with cross-sectional approach that aims to analyze the relationship between dysmenorrhea with student learning activities PSIK FK Unud. Samples were taken through a purposive sampling technique as many as 158 people. The data analysis using the Spearman Rank correlation test with a significace limit of 95% or ? = 0.05. The study was conducted at the Campus PSIK FK Unud on 17, 18, 24 and 25 March 2014, shows most respondents experienced moderate dysmenorrhea that 140 respondents (88.6%) and impaired learning activities were 108 respondents (68.4%). P value of 0.01(p <0.05) and r = 0.255, with a positive value, it can be concluded that there was a weak unidirectional relationship between dysmenorrhea with student learning activities at PSIK FK Unud in 2014.